Application of Circumstantial Evidence in Criminal Laws in Indonesia - Karunia Pangestu; Heru Suyanto; Rosalia Dika Agustanti (Jurnal Hukum Novelty, 2021)
Introduction to the Problem: Indonesia is a constitutional state; therefore, all citizens must obey the applicable regulations. If someone commits a criminal act and is required to be brought to the court, evidence is an important thing to resolve the criminal case. A judge can determine whether the accused is guilty or not, one of the ways to determine is to consider the evidence. The law of evidence is known to have two types of evidence, namely direct evidence and indirect evidence (circumstantial evidence). Circumstantial evidence is a kind of evidence in which the relationship between the facts that occur and the available evidence can only be seen after drawing some certain conclusions. Circumstantial evidence can be very important if the other evidences are not sufficient to prove a criminal case in a court. However, the circumstantial evidences must be in accordance with the other evidences.Purpose/Objective of the Study: The purpose of this study is to understand the circumstantial evidence in the perspective of criminal law and how it is applied in criminal cases.Design/Methodology/Approach: The research method used in this study is a normative juridical research method, with the statutory approach and conceptual approach. The type of data used in this study is the secondary data using three legal materials, namely primary legal materials, secondary legal materials and tertiary legal materials.Findings: Indirect evidence or Circumstantial evidence is one of the legal evidences according to Law Number 8 of 1981 concerning Criminal Procedure Law Article 188, namely the indication. However, Circumstantial Evidence is still rarely used by the system of criminal evidence in the courts in Indonesia because its validity is often questioned by the public.Paper Type: Research Article